Manajemen Keuangan Masjid di Kota Yogyakarta - Rizqi Anfanni Fahmi (Al-Tijary, 2017)
This study aims to describe the financial management practice in Yogyakarta City, Special Region of Yogyakarta. The data in this study were gathered by using questionnaires and analyzed by a simple qualitative descriptive approach. The study was conducted in 180 mosques by using area sampling because Yogyakarta City divided into 14 districts. Three main issues are focused: budget planning, fund management, and internal control. The result shows only 37,8% mosques have budget planning. The source of fund is dominated by Friday prayer infaq, while physical maintenance is the most expenditure. More than 90% of the mosques have a simple bookkeeping and financial report, although most of the mosques have not evaluated the budget regularly. This study reveals the average of the surplus balance is Rp 45,8 million idle and saved most in the conventional bank. It could be estimated the total amount of the mosque surplus balance in Yogyakarta City approximately Rp 22 billion. The study also found that 27 of 180 mosques have an economic empowerment program for the congregation.